Synthesis and characterisation of nanocrystalline ZrN PVD coatings on AISI 430 stainless steel - Taran, A. V.; Garkusha, I. E.; Taran, V. S.; Muratov, R. M.; Skoblo, T. S.; Romaniuk, S. P.; Starikov, V. V.; Baturin, A. A. (National Science Center "Kharkov Institute of Physics and Technology", 2019)
The nanocrystalline films of zirconium nitride have been synthesized using ion-plasma vacuum-arc deposition technique in combination with high-frequency discharge (RF) on AISI 430 stainless steel at 150oC. Structure examinations X-ray fluorescent analysis (XRF), X-ray diffraction analysis (XRD), scanning electron microscopy (SEM) with microanalysis (EDS), and transmission electron microscopy (TEM), nanoidentation method – were performed to study phase and chemical composition, surface morphology, microstructure and nanohardness of coatings. The developed technology provided low-temperature coatings synthesis, minimized discharge breakdown decreasing formation of macroparticles (MPs) and allowed to deposit ZrN coatings with hardness variation 26.6…31.5 GPa. It was revealed that ZrN single-phase coatings of cubic modification with finecrystalline grains of 20 nm in size were formed.
Keywords: zirconium nitride; spectrometer; mechanical properties; nanoindentation diagrams